PENGARUH PELAYANAN DAN KEPUASAN TERHADAP LOYALITAS NASABAH KREDIT PADA PT. BPR X - Faisal H Batubara (Politeknik APP Jakarta, 2018)
The purpose of this study is to determine how much influence between the services provided and the level of satisfaction obtained on loyalty of credit customers at PT. BPR X. Techniques used in collecting data is using the method of field observation, interviews to respondents and the distribution of questionnaires. The population used in this research is credit customers of PT. BPR X which amounted to 386 credit customers, sampling technique used is a purposive method obtained by the sample of 60 respondents or by 15% of the population. Methods of data analysis using multiple linear regression analysis, correlation test, determinant test, partial t test and multiple F test. The result of multiple linear regression analysis shows that Y = 0,254 + 0,474 X1 + 0,445 X2 meaning without Xeria veriabel (service) and X2 (satisfaction) then variable Y (satisfaction) remain 0,254. Based on the correlation test results of correlation value of 0,533 which means having a medium relationship in accordance with the criterion limits that have been determined at the correlation interval (0.40 - 0.59 category strong enough). The determinant test shows the value of R square of 0.284, which means the influence of service variables and satisfaction on the loyalty variable is 28.4%, the rest of 71.6 % is influenced by other independent variables which are not included in this research that is the level of competition, market demand , price, promotion, and so on. The result of t test is obtained by t value of service variable (2,169)> t-table (1,671) with significance value 0,034 below 0,05 hence it shows that service variable does not have significant influence to loyalty and obtained value t-count variable customer satisfaction (3.653)> t-table (1,671) with a significance value of 0.001 below 0.05 then it shows that customer satisfaction variables does not significantly influence loyalty. The result of F test shows that service (X1) and customer satisfaction (X2) have positive effect and significant on Customer loyalty (Y), this is proven by F test calculation obtained F count = 11,313 bigger than Ftable 2,370. The significant level obtained is (0,000) this value can be said to be absolutely significant because it is valued at 0,000 and smaller than the significant standard (5% or 0.05)